Investigation of structural, electrical and optical properties of doped dilute GaAsBi grown by molecular beam epitaxy - Alhassan, Sultan (2022)
This thesis reports an investigation of the strutural, electrical and optical properties of dilute bimuth (Bi) containing semiconductors materials, namely GaAsBi grown by Molecular Beam Epitaxy (MBE) on GaAs substrates at low temperature. It is well known that the addition of a few percent of Bi in GaAs compound semiconductors has been shown to dramatically reduce the energy bandgap of host material. This remarkable bandgap reduction has several applications in long-wavelength lasers, solar cells, and photonic devices. However, the insertion of these impurity atoms causes defect levels in the bandgap of semiconductor materials. These can have serious effects for the quality of the material, for example, they can reduce charge carrier lifetime and reduce optical efficiency. Indeed, determining the nature and features of the defects existing in the materials, which is critical for many device applications, will improve and help in understanding their implications on the quality of materials and devices performance. In this work, an investigation will be reported on the effect of the orientation of the substrates on the structural, electrical and optical properties of dilute GaAs1−xBix epilayers structures having a Bi composition x = ~5.4%, grown by MBE on (100) and (311)B GaAs planes. The results of this study show that the detected defects affected significantly the electrical and optical properties of semiconductor structures and devices. In particular, X-ray diffraction results revealed that the in-plane strain in the Ga(As,Bi) layer of the samples grown on (100)-oriented substrates is significantly larger than that of the samples grown on (311)B-oriented substrates. Deep Level Transient Spectroscopy (DLTS) measurements showed that the number of electrically active traps were different for the two GaAs substrate orientations. In particular, three and two electron traps are detected in samples grown on (100) and (311)B GaAs substrates, respectively, with activation energies ranging from 0.12 to 0.41 eV. The observed traps with small activation energies are attributed to Bi pair defects. The photoluminescence (PL) and Raman spectra have evidenced different compressive strain which affects considerably the optical properties. In addition, a further investigation was carried out to study the effect of gamma radiation dose on the electrical and optical properties of dilute GaAsBi layer grown by MBE on a highly doped (100) GaAs substrates. The DLTS revealed that after irradiation the number of electrically active traps decreased. Four, three and two electron traps were detected in as-grown and irradiated samples with 50 kGy and 100 kGy doses, respectively. The PL intensity of the main peak was found to increase with the irradiation dose, evidencing an enhancement of the optical properties and annihilation/contributions of Bi- related traps, and supporting the electrical results. Additionally, this thesis reports the structural and optical properties of n-type Si-doped and p-type Be-doped GaAs1−xBix thin films grown by MBE on (311)B GaAs substrates. The experimental studies demonstrate that, the composition of Bi incorporated in both n-type and p-type doped GaAsBi was similar, despite that the samples present remarkable differences in the number of Bi related defects, non-radiative centers and alloy disorder. Particularly, the results evidence that the Bi-related defects in n- and p-doped GaAsBi alloys have important impact on the differences of their optical properties.